P1166Women as candidates for CRT: Are they less but better?. (18th June 2020) - Aguiar-Ricardo, I; Nunes-Ferreira, A; Rigueira, J; Rdrigues, T; Cunha, N; Antonio, P S; Morais, P; Pereira, S C; Bernardes, A; Santos, I; Magalhaes, A; Neves, H; et al.
Abstract: Introduction:  Women have been under-represented in trials of cardiac resynchronization therapy (CRT).  Most available data suggest that CRT has a greater clinical benefit in women than in men. However, further studies are needed to investigate the exact reasons for these results. Purpose: To compare the prognostic impact and response rate of CRT in women and man. Methods: Prospective study, single-center study that included pts undergoing CRT implant from 2015 to 2019. Clinical and echocardiographic evaluation were made before CRT implant and between 6-12 months post-implant. Pts with EF elevations≥10% or LV end-systolic volume (ESV) reductions≥15% were classified as responders. Patients with EF elevations ≥ 20% or ESV reductions≥30% were classified as super-responders. All the parameters were compared between women and man. Prognostic impact of CRT was evaluated as total mortality by the Cox regression and Kaplan-Meier methods. Results: From 2015-2019, 561 patients were submitted to CRT implant with a follow-up duration of 18.9 ± 15.8 months. From these 148 (26.4%) were female (mean age 72.2 ± 10 years, 22.4% ischemic, LVEF < 30% in 70.2%). The cardiovascular risk factors and comorbidities were similar in both populations (women and men). In the female group, dilated cardiomyopathy was more frequent than in men (71% vs 50.8%, p < 0.01), with ischemic heart disease being the second most frequent etiology of heart failure. The frequency of LBBB was similar in both groups (63.9% in women and 57.0% in men, p = NS) however the QRS duration was higher in women (164 ± 17 vs 160 ± 24, p = 0.017). The baseline mean EF was similar (30.5 ± 10.3ms in women and 30.3 ± 11.4ms in men) but the ESV was lower (109.7 ± 59.9 vs 138.4 ± 64.6, p < 0.001). The prevalence of complications and need for surgical revision were similar in both groups. The rate of CRT responders was similar in both groups, although tendentially higher in women (64.3% in women vs 55.2% in men, p = NS). On the other hand, super-responder rate was statistically significant (38% in women vs 25.1% in men, p = 0.004). The long-term survival was similar in both groups. Conclusion: The rate of super-responders was higher in women than in men. This may be explained by the higher prevalence of dilated cardiomyopathy in this subgroup of patients and by the fact that women have smaller hearts and a larger QRS duration at baseline, most likely to have a real LBBB. Long-term mortality of CRT was not gender related